Komodifikasi Agama dalam Era Digital (Studi Etnografi Virtual Fenomena Cek Khodam di Media Sosial) - Fuadi, Muhamad Hanif Fuadi; Ramadhanita, Frista Fitriany (Departemen Komunikasi dan Penyiaran Islam, 2025)
This study examines the phenomenon of religious commodification in the digital era, focusing on the practice of checking khodam on social media. Using a virtual ethnographic approach, the study analyzes how traditional spiritual practices are transformed into digital commodities. The results of the study show that khodam checks on social media are a form of religious commodification that involves commercialization, standardization, and personalization of spiritual services. This phenomenon reflects a shift in religious practices in the digital society and raises questions about authenticity and ethics in online spirituality.